The Impact of Sacubitril / Valsartan Versus ACE/ARB Therapy on Functional Capacity in Heart Failure with Reduced Ejection Fraction - Mohammad Yassen (Translation, 2023)
Please view the PDF to see the formatted meeting abstract.